2016
DOI: 10.1186/s12870-016-0851-z
|View full text |Cite|
|
Sign up to set email alerts
|

A novel role for STOMATAL CARPENTER 1 in stomata patterning

Abstract: BackgroundGuard cells (GCs) are specialised cells within the plant epidermis which form stomatal pores, through which gas exchange can occur. The GCs derive through a specialised lineage of cell divisions which is specified by the transcription factor SPEECHLESS (SPCH), the expression of which can be detected in undifferentiated epidermal cells prior to asymmetric division. Other transcription factors may act before GC specification and be required for correct GC patterning. Previously, the DOF transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
(83 reference statements)
1
10
0
Order By: Relevance
“…In summary, 11 of the TFs (PDF2, SBF, WUSCHEL, TESMIN/TSO1-like CXC, KANADI1, GLK, DOF5.7, LHY, repressor AS1/AS2, GBF1, STK) that were predicted to bind the promoter regions of most of the analyzed Msrs act in plant growth and regulation. Studies have demonstrated that the above TFs are involved in shoot development [40], lateral root formation and development [41], embryo development [40], leaf development [42,43], stomata patterning [44], chloroplast development [45], the development of reproductive tissues [46], early embryogenesis [47], seedling development [48], senescence [49], the regulation of circadian rhythms [50], and cell-cycle-dependent transcription-enabling plant growth [47]. Interestingly, seven of the TFs that are listed in Table 2 (WUSCHEL, DIVARICITA, BELLRINGER, HB32 and HB34, RAP2.7, CRABS CLAW, ODO1) control the flowering process by regulating floral development [51,52], fragrance [53], and nectary development [54] and the initiation and repression of flowering [47,49,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, 11 of the TFs (PDF2, SBF, WUSCHEL, TESMIN/TSO1-like CXC, KANADI1, GLK, DOF5.7, LHY, repressor AS1/AS2, GBF1, STK) that were predicted to bind the promoter regions of most of the analyzed Msrs act in plant growth and regulation. Studies have demonstrated that the above TFs are involved in shoot development [40], lateral root formation and development [41], embryo development [40], leaf development [42,43], stomata patterning [44], chloroplast development [45], the development of reproductive tissues [46], early embryogenesis [47], seedling development [48], senescence [49], the regulation of circadian rhythms [50], and cell-cycle-dependent transcription-enabling plant growth [47]. Interestingly, seven of the TFs that are listed in Table 2 (WUSCHEL, DIVARICITA, BELLRINGER, HB32 and HB34, RAP2.7, CRABS CLAW, ODO1) control the flowering process by regulating floral development [51,52], fragrance [53], and nectary development [54] and the initiation and repression of flowering [47,49,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the stomatal density and index of ggl7ggl14ggl26 triple mutant were not different from those in ggl14 ( Supplementary Figures S6A , B ), suggesting that GGL7 and GGL26 are not involved in stomatal density. It has been reported that some guard cell-expressed genes affect stomatal patterning and shape ( Lee et al, 2013 ; Negi et al, 2013 ; Castorina et al, 2016 ; Rui et al, 2017 ). We found that the one-spacing rule in these single, double, and triple mutants was not disrupted (data not shown), suggesting that these GGLs are not involved in this stomatal developmental process.…”
Section: Resultsmentioning
confidence: 99%
“…Antagonistically, Castorina et al (2016) performed comprehensive analysis of the control of SCAP1 expression during leaf development and found that the transcriptional component SCAP1 is essential in the genetic pathway of stomatal production and might be a key regulator involving SCAP1 mediated down regulation of EPF2 activation. SCAP1 plays a spatially distinct role in the GC maturation, as well as has the fundamental role in GC patterning and function.…”
Section: Involvement Of Scap1 In Functional Stomata Developmentmentioning
confidence: 99%